Biliary Dysfunction in Children with Iron Deficiency - Yu.V. Marushko; K.I. Nahorna (Zaslavsky O.Yu., 2016)
Background. Functional disorders of the biliary tract (FDBT) remain a topical problem of pediatric gastroenterology due to the high incidence and progressive course with formation of chronic cholecystitis and cholelithiasis in patients. Iron deficiency (ID) has a well-known effect on the course of the gastrointestinal tract pathology. With the aim of evaluating the state of the biliary system and clinical features of FDBT associated with ID, a case-control study was conducted in 160 children aged 9 to 17 years, who underwent in-patient treatment for exacerbation of biliary tract pathology. According to the iron metabolism tests, children were divided into 3 groups: I - 29 children with FDBT and I degree anemia; II - 91 children with FDBT and latent ID; III - 40 children with FDBT and normal iron metabolism parameters. Research methods included: the study of anamnesis, clinical examination, complete blood count, serum iron level, total iron-binding capacity, calculation of percent transferrin saturation, ultrasound of the abdominal organs and dynamic ultrasound cholecystography with choleretic breakfast. Results. The study found that children with FDBT and ID have a higher incidence of FDBT exacerbations, increased intensity of dyspeptic and asthenovegetative symptoms in case of FDBT exacerbation, increase in size, reduced contractile function of gallbladder (GB) and hypotonic-hypokinetic FDBT type. Conclusions. Children with FDBT and ID have burdened course of FDBT due to the high incidence of exacerbations, severe dyspeptic and asthenovegetative symptoms in the acute phase, as well as reduced contractile function of GB and hypotonic-hypokinetic FDBT type, which is clinically unfavorable because of the risk of biliary sludge and cholelithiasis.